Knowledge, attitude and practice of menstrual cup among female medical students in private medical college - Brindhaavanan, Pavithra Gangadharan; Ranganadhan, Prateeksha; Boominathan, Charumathi; Parasuraman, Gomathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Menstrual cups have been available for decades, but their use in India is limited because of the popularity of sanitary pads. Menstrual cups are a safe and feasible alternative to the more widely used sanitary napkins. Objective of this study was to assess menstrual cup awareness among the female medical college students. Methods: A cross sectional study was conducted on 389 undergraduate female medical students, among which 355 students responded after consent. Data was collected through Google forms using pre-tested semi structured questionnaire. Collected data was transferred to Microsoft excel and was analysed using statistical package for the social sciences (SPSS) version 21. Chi-square test was used to determine the association. Results: Among the 355 female medical students, 215 (60%) of them belonged to upper middle class. 335 (94%) of them were unmarried. (282) 80% of the students had knowledge regarding menstrual cups, in which majority were aware of the material used to manufacture the cups. The cup was preferred by 100 (28%) and 54 (15%) of them used menstrual cups for its comfort, easiness to wear and less odor. Few of them had pain, dryness and rashes after the use of menstrual cup. Problem of leakage was encountered in 15-26%. There was significant association between income and usage of menstrual cup (p<0.05). Conclusions: Menstrual cup is a cost-effective and eco-friendly alternative to tampons and sanitary napkins. Menstrual cup also appears to be a comfortable, safe and efficient option for menstrual hygiene. Due to the popularity and promotion of napkins, there is lack of awareness on menstrual cups. So, awareness programs must be conducted to enlighten the benefits on usage of menstrual cups, so as to promote menstrual health and hygiene.